Gambaran Status Besi Tubuh pada Wanita Penderita Anemia di RSUP Dr. Sardjito - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
The state of body iron in women anemic patients at Dr. Sardjito General Hospital Disorders resulting from body iron overload (hemosiderosis in reticgoendothelial cells or accumulation within parenchymal cells of the liver, heart and other organs) may octal- in patients who have undergone frequent blood transfusions or under other excessive iron therapy to treat the anemia. Therefore, every iron preparation especially by repeated parenteral route or blood transfusions must be accompanied by monitoring of body iron status. In the present study the most useful indirect measurement of ,body iron status, included serum ferritin (SF), serum iron (SI), total iron binding capacity (TIBC), transferin saturation (TS) and the erythrocyte, were studied in 34 women anemic patients at the Dr. Sardjito General Hospital. The results of the study are as follows: among 30 subjects with anemia caused by other than iron deficiency, included chronic renal diseases, inflammation or infection, hematologic and other organ malignancy, idiopathic thrombocytopenic purpura, the mean of SF level increased to 210,85ng/ml